Extension Design for Making Jackfruit Banana Flour Cookies in Tambaksari Village, Purwodadi Sub-District, Pasuruan District - Da Conceicao, Vicensia Fatima; Gunawan, Gunawan; Rahmi, Ainu (CV. Komunitas Dunia Peternakan, 2024)
Jackfruit banana in Tambaksari Village is the dominant variety with a high yield productivity of 4 tons/ha. However, the utilization of these bananas is not optimal, so an innovation was developed to utilize raw jackfruit banana fruit into jackfruit banana flour to be processed into cookies. This study aims to design extension services, analyze the increase in knowledge, and determine the level of skills and attitudes of 15 members of Women Farmers Group Sri Rejeki regarding the making of jackfruit banana flour cookies in Tambaksari Village, Purwodadi District, Pasuruan Regency from February to April 2024. The research method used a qualitative approach with a Level III action research method. The process of implementing Extension includes the stages of planning, action, observation, and reflection. Based on observations and interviews, there are significant changes in behavior supported by simple quantitative data from the results of the first evaluation, which shows an increase in knowledge from the value of increasing knowledge percentage of 59%, the level of attitude with a percentage value of 85% (responsible category), and the level of skills getting 12 skilled people. The second evaluation shows the value of increasing knowledge percentage of 60%, the level of attitude with a percentage value of 86% (responsible category), and the level of skills getting 10 skilled people. The conclusion of this research is that this extension is effective in increasing the knowledge, skill level, and attitude level of Women Farmers Group members in making jackfruit banana flour cookies.